Lanzamiento de cafetería Atemporal - Flores Llanco, Karen Kristell (2023)
This project consists of carrying out the launch campaign of a new chain of cafés called "Atemporal", that is aimed at young people and young adults in Lima Metropolitana Lima, Perú and aims to position the brand as an authentic and welcoming café, which provides a complete experience and offers a unique experience awakening your senses for maximum pleasure and comfort.